Postnatal Establishment of Allelic Gαs Silencing as a Plausible Explanation for Delayed Onset of Parathyroid Hormone Resistance Owing to Heterozygous Gαs Disruption. (March 2014) - Turan, Serap; Fernandez‐Rebollo, Eduardo; Aydin, Cumhur; Zoto, Teuta; Reyes, Monica; Bounoutas, George; Chen, Min; Weinstein, Lee S; Erben, Reinhold G; Marshansky, Vladimir; Bastepe, Murat
ABSTRACT Pseudohypoparathyroidism type‐Ia (PHP‐Ia), characterized by renal proximal tubular resistance to parathyroid hormone (PTH), results from maternal mutations of GNAS that lead to loss of α‐subunit of the stimulatory G protein (Gαs) activity. Gαs expression is paternally silenced in the renal proximal tubule, and this genomic event is critical for the development of PTH resistance, as patients display impaired hormone action only if the mutation is inherited maternally. The primary clinical finding of PHP‐Ia is hypocalcemia, which can lead to various neuromuscular defects including seizures. PHP‐Ia patients frequently do not present with hypocalcemia until after infancy, but it has remained uncertain whether PTH resistance occurs in a delayed fashion. Analyzing reported cases of PHP‐Ia with documented GNAS mutations and mice heterozygous for disruption of Gnas, we herein determined that the manifestation of PTH resistance caused by the maternal loss of Gαs, ie, hypocalcemia and elevated serum PTH, occurs after early postnatal life. To investigate whether this delay could reflect gradual development of paternal Gαs silencing, we then analyzed renal proximal tubules isolated by laser capture microdissection from mice with either maternal or paternal disruption of Gnas. Our results revealed that, whereas expression of Gαs mRNA in this tissue is predominantly from the maternal Gnas allele at weaning (3 weeks postnatal) and in adulthood, the contributions of the maternal and paternal Gnas alleles to Gαs mRNA expression are equal at postnatal day 3. In contrast, we found that paternal Gαs expression is already markedly repressed in brown adipose tissue at birth. Thus, the mechanisms silencing the paternal Gαs allele in renal proximal tubules are not operational during early postnatal development, and this finding correlates well with the latency of PTH resistance in patients with PHP‐Ia. © 2014 American Society for Bone and Mineral Research.